Explanation:
Simplifying
10x + -4 = 6x + 8
Reorder the terms:
-4 + 10x = 6x + 8
Reorder the terms:
-4 + 10x = 8 + 6x
Solving
-4 + 10x = 8 + 6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
-4 + 10x + -6x = 8 + 6x + -6x
Combine like terms: 10x + -6x = 4x
-4 + 4x = 8 + 6x + -6x
Combine like terms: 6x + -6x = 0
-4 + 4x = 8 + 0
-4 + 4x = 8
Add '4' to each side of the equation.
-4 + 4 + 4x = 8 + 4
Combine like terms: -4 + 4 = 0
0 + 4x = 8 + 4
4x = 8 + 4
Combine like terms: 8 + 4 = 12
4x = 12
Divide each side by '4'.
x = 3
Simplifying
x = 3